Is there a price bubble in the exchange rates of the developing countries? The case of BRICS and Turkey - Hakan Yildirim; Saffet Akdag; Andrew Adewale Alola (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - The last decades have experienced increasingly integrated global political and economic dynamics ranging especially from the influence of exchange rates and trade amid other sources of uncertainties. The purpose of this study is to examine the exchange rate dynamics of Brazil, Russia, India, China, and South Africa (BRICS) and the Republic of Turkey. Design/methodology/approach - Given this perceived global dynamics, the current study examined the BRICS countries and the Republic of Turkey's exchange rate dynamics by using the United States (US) monthly dollar exchange rate data between January 2002 and August 2019. The price bubble which is expressed as exceeding the real value of assets' prices which is observably caused by speculative movements is investigated by using the Supremum Augmented Dickey-Fuller (SADF) and the Generalized Supremum Augmented Dickey-Fuller (GSADF) approaches. Findings - Accordingly, the GSADF test results opined that there are price bubbles in the dollar exchange rate of other countries except for the United States Dollar (USD)/Indian Rupee (INR) exchange rate. As the related countries are classified as developing countries in terms of their structure, they are also expectedly the subject of speculative exchange rate movements. Speculative movements in exchange rates may cause serious problems in national economies. Originality/value - Thus, the current study provides a policy framework to the BRICS countries and the Republic of Turkey.
Keywords: C22; D51; G12; G17; 330; Price bubble; Currency conversion rates; SADF; GSADF; BRICS; Turkey